CAFF CBMP Report No.12 - A Strategy for Developing Indices and Indicators to Track Status and Trends in Arctic Biodiversity - Gill, M. (Conservation of Arctic Flora and Fauna Working Group (CAFF), 2008)
Arctic Council's CAFF Working Group Circumpolar Biodiversity Monitoring Program Report No.12 - A Strategy for Developing Indices and Indicators to Track Status and Trends in Arctic Biodiversity